2005
DOI: 10.1090/s0002-9947-05-03773-6
|View full text |Cite
|
Sign up to set email alerts
|

Root invariants in the Adams spectral sequence

Abstract: Abstract. Let E be a ring spectrum for which the E-Adams spectral sequence converges. We define a variant of Mahowald's root invariant called the 'filtered root invariant' which takes values in the E 1 term of the E-Adams spectral sequence. The main theorems of this paper are concerned with when these filtered root invariants detect the actual root invariant, and explain a relationship between filtered root invariants and differentials and compositions in the E-Adams spectral sequence. These theorems are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 36 publications
(92 reference statements)
0
40
0
Order By: Relevance
“…Subsequent work of Sadofsky [33] showed that for p > 3 one has β k ∈ M cl (α k ). Computations of Behrens at p = 3 [5] and later at p = 2 [6] provided further evidence that the classical Mahowald invariant of a v n -periodic class in the stable stems is v n+1 -periodic. In this paper, we will produce motivic analogs of Mahowald and Ravenel's computations of the Mahowald invariant of 2 i for i ≥ 1.…”
Section: Introductionmentioning
confidence: 86%
“…Subsequent work of Sadofsky [33] showed that for p > 3 one has β k ∈ M cl (α k ). Computations of Behrens at p = 3 [5] and later at p = 2 [6] provided further evidence that the classical Mahowald invariant of a v n -periodic class in the stable stems is v n+1 -periodic. In this paper, we will produce motivic analogs of Mahowald and Ravenel's computations of the Mahowald invariant of 2 i for i ≥ 1.…”
Section: Introductionmentioning
confidence: 86%
“…• For p = 3 we have R(α i ) = β h i for i ≤ 6, and we have R(α i ) = β i for for i ≡ 0, 1, 5 (mod 9) (see Behrens [2]).…”
Section: Mark Behrensmentioning
confidence: 99%
“…Then, apply the forgetful functor to the nonequivariant world. Bruner and Greenlees [BG95] proved that this construction produces the classical Mahowald invariant 𝑀(𝛼) of 𝛼, which has been studied extensively by Mahowald, Ravenel, and Behrens [MR93,Beh06,Beh07].…”
Section: Sketch Of Proofmentioning
confidence: 99%